Mobs and Microbes Global Perspectives on Market Halls, Civic Order and Public Health - Farah, Leila Marie; Martin, Samantha (Leuven University Press, 2023)
Market halls at the intersection of civic order and public health. Markets and market halls have always been more than about trade and nourishment. A detailed look at the histories of marketplaces provides evidence of the public health concerns they faced, as well as the social commotion, mobilization and, at times, unrest they hosted. This edited volume reappraises the market hall, examining both its architectural and its social and political significance. Focusing on how these buildings embodied transformations in architecture and urbanism from the mid-nineteenth century until the age of COVID-19, Mobs and Microbes situates market halls at the intersection of civic order and public health. Central to this are advances in sanitation and hygiene. These radical interventions also mediated conflicting interests. Through their rational designs, market halls intertwined government policies and regulations, which formalized, controlled and literally imposed order. Additionally, markets served as demonstration grounds for community-led mobilization efforts. With case studies spanning North America, Europe, Asia, India and Africa, this edited volume provides a global perspective on covered market halls across many disciplines, including architecture, history of art and architecture, landscape architecture, food studies and urban history.